2005
DOI: 10.1227/01.neu.0000170987.14821.6f
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral Calcinosis of the Filum Terminale

Abstract: This is the first known case of intradural involvement by tumoral calcinosis. This is an uncommon disorder, and a high index of suspicion is required to diagnose the condition, which can recur if incompletely removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In the literature, masses of calcifications of the filum terminale requiring surgical removal have been described in a case of tumoral calcinosis [12] and in a case of gouty tophi in the filum terminale in a patient without systemic gout [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, masses of calcifications of the filum terminale requiring surgical removal have been described in a case of tumoral calcinosis [12] and in a case of gouty tophi in the filum terminale in a patient without systemic gout [13].…”
Section: Discussionmentioning
confidence: 99%
“…This case presents a diagnostic challenge because of the mode of presentation and the nature of the lesion (2).…”
Section: P I C T U R E 1 A: L U Mb a R Ct -S C A N S H O Wi N G A Nmentioning
confidence: 99%
“…Our patient had concurrent unidentified serology negative spondyloarthropathic connective tissue disease, and the calcinosis type of the patient was probably type 3. Few cases of tumoral calcinosis due to scleroderma have been reported (4,8,11). Durant et al (2) studied 21 patients with tumoral calcinosis.…”
Section: Treatmentmentioning
confidence: 99%
“…Tumoral calcinosis involving the lumbar spine is rare; to our knowledge, only 9 studies on lumbar tumoral calcinosis have been reported in the literature (1,2,7,8,9,11,13,14,15). The lesions involved the vertebral bodies, facet joints, dura, and filum terminale (1,2,8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation